Absence of true long-range orbital order in a two-leg Kondo ladder - Xavier, J. C.; Malvezzi, André Luiz [UNESP] (Amer Physical Soc, 2007)
We investigate, through the density-matrix renormalization group and the Lanczos technique, the possibility of a two-leg Kondo ladder presenting an incommensurate orbital order. Our results indicate staggered short-range orbital order at half-filling. Away from half-filling our data are consistent with incommensurate quasi-long-range orbital order. We also observed that an interaction between the localized spins enhances the rung-rung current correlations.